Fabrication and morphological characterization of Nafion thin films spin coated on silica - Palisoc, Shirley T. (Animo Repository, 2014)
Nafion thin films (∼1 μm) were fabricated via the spin coating technique. Angular velocity and concentration of Nafion solution were chosen as parameters and were varied in order to determine thickness relationships. Energy-Dispersive Spectroscopy (EDS) and Scanning Electron Microscopy (SEM) characterizations were performed in order to determine elemental composition and surface morphology of the films respectively.